Effects of aminophylline therapy on urine output and renal function in children with acute kidney injury in an African setting - Nyann, Beatrice Irene (Department of Paediatrics and Child Health, 2022)
Background Acute kidney injury (AKI) is a frequent complication of children admitted to the paediatric intensive care unit and is associated with significant short term and long -term consequences. The causes vary from conditions that decrease intravascular volume to the use of nephrotoxic medications. One key management modality of AKI is the use of diuretics to reduce fluid overload which is an important indication for initiation of renal replacement therapy (RRT) - dialysis and also an important indicator of morbidity and mortality. Aminophylline, a drug that is well known for its use in the treatment of bronchial asthma is also purported to have diuretic effects on the kidneys. A paucity of data to support the use of aminophylline as diuretic and especially in children has occurred until a recent renewal of interest in this drug as a diuretic. In the Paediatric intensive care unit (PICU) of the Red Cross War Memorial Children's Hospital (RCWMCH), the use of aminophylline to augment urine output started in the early 2000s.This retrospective case-cross over study assesses the effect aminophylline in critically ill children with AKI; specifically, the effect on urine output, improvements in serum creatinine levels or limitations of renal replacement therapy as well as any age-related differences in aminophylline effects. Methods Children admitted to the PICU of RCWMCH with AKI (from 2012 to June 2018) were identified through a search of the PICU database, folders of cases were obtained, and a folder review carried out. Cases that fulfilled the inclusion criteria (that is children admitted to PICU with AKI who received aminophylline) were subsequently recruited. Data captured and analyzed included demographics, underlying disease conditions, medications, vital signs, urine output, renal function, arterial blood gases, RRT and outcomes of AKI. Results Thirty-five children were analyzed. Urine output increased from a median of 0.4mls/kg/hr [IQR: 0.1, 1.1] at six hours prior to aminophylline administration to 0.6mls/kg/hr[IQR: 0.2, 1.9] at six hours post aminophylline therap,1.0mls/kg/hr(IQR:0.2, 2.7) after twelve hours and 1.6 mls/kg/hr(IQR:0.2, 4.2) after twenty-four hours and this was statistically significant based on the Friedman's analysis of variance test (p=0.001).The median change in postaminophylline urine output after six hours was 0.05mls/kg/hr (IQR:0.0, 0.6) and this change did not vary significantly across the age groups (p=0.530). There was no significant change in serum creatinine levels six hours pre and post- aminophylline administration [109(77,227), 125.5(82,200) micromole/l] respectively, p=0.135. Sixteen out of the thirty-five children (45.7%) required renal replacement therapy.